KESIAPAN KELEMBAGAAN KELOMPOK TANI HUTAN DESA KAWENDE KECAMATAN POSO PESISIR UTARA KABUPATEN POSO DALAM RENCANA PEMBANGUNAN HUTAN KEMASYARAKATAN - Hadidja, Hadidja; Golar, Golar; Sudhartono, Arief (Universitas Tadulako, 2016)
The readiness of farmer association institution and interaction of farmers association with in charge institution is an important element in developing community forest. The development of Community Forest in Kawende village started by people’s unrest about forest in their village that has suffered a distruction. The research was conducted for 3 months that began on September to November 2014 on two farmers associations of community Forest in Kawende village North Coastal Poso subdistrict, Central Sulawesi. The research began by doing observation in location and interview directly by choosing respondend directly (Purposive Sampling). The Instrument that used in the research was people and and questions list for interviewing and also stationary and camera. The data Analysis used was institutional analysis that more stressed on institutional structure and the rules that related to the ownership right and forest utilization (Ostrom, 1990 in Iqbal, M. 2009) by requiring primary data from interview and secondary data from the institution and literature review. The result of the research showed the villagers of Kawende had institution in form of organisation but the rule of the ownership and forst utilization still in charge of Forestry Department of Poso District. The relation between farmers Association as candidates of Community Forest manager with involved institution was very good, it was known by the one who facilitated people ideas was Forestry Department of Poso District and Department of Riverflow Area Management of Palu-Poso.Keywords : Farmers Association, Readiness, Institution, CommunityForets